2014
DOI: 10.1149/2.027405jss
|View full text |Cite
|
Sign up to set email alerts
|

Pad Scratching in Chemical-Mechanical Polishing: The Effects of Mechanical and Tribological Properties

Abstract: In chemical-mechanical polishing (CMP), even the soft pad asperities may, under certain conditions, generate scratches on the relatively hard surfaces being polished. In the present study, contact mechanics models of pad-induced scratching are formulated, and the effects of the hardness of the surface layers and of pad asperities as well as the interfacial friction are elucidated. Additionally, scratch-regime maps are proposed to provide criteria for scratching hard surface layers by the softer pad asperities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The wafer is modeled as a linearly elastic material before yield. It has been shown that the polishing pad material plastically deforms and has time dependent mechanical behavior in CMP [3,[9][10][11]. The desired result of this analysis is to determine the elementary contact mechanics variables that influence scratch production.…”
Section: Wafer Stress Field Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The wafer is modeled as a linearly elastic material before yield. It has been shown that the polishing pad material plastically deforms and has time dependent mechanical behavior in CMP [3,[9][10][11]. The desired result of this analysis is to determine the elementary contact mechanics variables that influence scratch production.…”
Section: Wafer Stress Field Analysismentioning
confidence: 99%
“…Equation 9 provides the yield criterion for a relatively soft elastic sliding pad asperity over the harder wafer surface [3,14,15].…”
Section: Wafer Stress Field Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the theoretical and experimental work on monolithic layers, it has been found that scratching by pad asperities strongly depends on the pad-to-layer hardness ratio and the interfacial friction between the pad asperities and the surface layers [13]- [16].…”
mentioning
confidence: 99%